Analytical parameter identification for a viscoplastic material model for structural adhesive bonds - Striewe, Marius; Schmelzle, Lars; Possart, Gunnar; Meschut, Gerson; Mergheim, Julia; Teutenberg, Dominik (Journal of Adhesion Science and Technology)

Experimental investigation of local joining element kinematics in mechanical joints and surrogate modelling for crash applications - Bähr, Philipp; Striewe, Marius; Dargel, Alrik; Sommer, Silke; Hein, David; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
Subject of this paper is the investigation of the influence of local joint kinematics on the load-bearing and failure behavior of self- piercing riveted (SPR) joints. It can be shown that the local joint kinematics of SPR joints correlate with the failure mechanism of the joint. The kinematics are highly influenced by the material properties of the joining partners. Detailed experimental results from tensile tests on a representative SPR joint are presented, with local joint kinematics quantified using multiple complementary measurement methods (optical measurement, micrographs, in situ computer tomography). Furthermore, results of component tests are shown where the kinematics of the joints have been measured in the same manner. The experimental results are later used to calibrate simulation models for crash application which are used to simulate the specimen and component tests. The results of the investigation show that the local joint kinematic influences the failure behavior of the joint. Simulations of the experimental tests have shown good results, and the investigated models are able to predict the actual joint behavior.

Testing, modelling and parameter identification for adhesively bonded joints under the combined influence of temperature and strain rate - Schmelzle, Lars; Striewe, Marius; Mergheim, Julia; Meschut, Gerson; Possart, Gunnar; Teutenberg, Dominik (Journal of Adhesion Science and Technology)

Influence of Liquid metal embrittlement on load-bearing capacity of resistance spot welds under crash loads: A study based on S-Rail components - Yang, Keke; Biegler, Max; Happe, Linus; Striewe, Marius; Olfert, Viktoria; Hein, David; Rethmeier, Michael; Meschut, Gerson (Materials Research Proceedings)
Abstract. Liquid Metal Embrittlement (LME) cracking is a well-documented issue encountered during resistance spot welding (RSW) of zinc-coated advanced high-strength steels (AHSS) in automotive manufacturing. Given that existing research has predominantly focused on laboratory-scale samples and lacks investigation into the load-bearing capacity of joints under crash conditions, this study aims to fill these gaps by analyzing third-generation zinc-coated AHSS. S-Rail components were produced through stamping to replicate real-world manufacturing conditions and geometries of automotive parts. To account for the disturbances typically encountered in production, samples with LME cracks were intentionally fabricated. Subsequently, a modified three-point bending test, assisted by numerical simulations, was developed to effectively apply loads to the weld spots of the S-Rail components. Results from crash tests demonstrated that observed light crack severity does not significantly compromise the joint's load-bearing capacity or lead to earlier joint failure.

Ersatzmodellentwicklung zur Berücksichtigung der lokalen Fügeelementkinematik in mechanisch gefügten Verbindungen für die Bauteilauslegung im stahlintensiven Karosseriebau - Striewe, Marius; Bähr, Philipp; Meschut, Gerson; Hein, David; Sommer, Silke (14. Kolloquium: Gemeinsame Forschung in der Mechanischen Fügetechnik)

Experimentelle und numerische Untersuchung des Einflusses variabler Betriebstemperaturen auf das Trag- und Versagensverhalten struktureller Klebverbindungen unter Crashbelastung - Schmelzle, Lars; Mergheim, Julia; Possart, Gunnar; Striewe, Marius; Meschut, Gerson (23. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Ersatzmodellentwicklung zur Berücksichtigung der lokalen Fügeelementkinematik in mechanisch gefügten Verbindungen für die Bauteilauslegung im stahlintensiven Karosseriebau - Bähr, Philipp; Striewe, Marius; Meschut, Gerson; Sommer, Silke; Hein, David (13. Kolloquium: Gemeinsame Forschung in der Mechanischen Fügetechnik)

Methode zur Simulation des temperaturabhängigen Crashverhaltens von strukturellen Klebverbindungen - Striewe, Marius; Teutenberg, Dominik; Hein, David; Meschut, Gerson; Schmelzle, Lars; Mergheim, Julia; Possart, Gunnar (Klebtechnische Doktorandenseminare 2020 - 2022)

Experimentelle und numerische Untersuchung des Einflusses variabler Betriebstemperaturen auf das Trag- und Versagensverhalten struktureller Klebverbindungen unter Crashbelastung - Striewe, Marius; Meschut, Gerson; Schmelzle, Lars; Mergheim, Julia; Possart, Gunnar; Steinmann, Paul (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Ersatzmodellentwicklung zur Berücksichtigung der lokalen Fügeelementkinematik in mechanisch gefügten Verbindungen für die Bauteilauslegung im stahlintensiven Karosseriebau - Bähr, Philipp; Striewe, Marius; Meschut, Gerson; Sommer, Silke (12. Kolloquium: Gemeinsame Forschung in der Mechanischen Fügetechnik)

Testing, modelling, and parameter identification for adhesively bonded joints under the influence of temperature - Schmelzle, Lars; Striewe, Marius; Mergheim, Julia; Meschut, Gerson; Possart, Gunnar; Teutenberg, Dominik; Hein, David; Steinmann, Paul (Journal of Adhesion Science and Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanics of Materials; General Chemistry

Investigation of ductility and fracture behavior of EN AW-5182 H18 at non-isothermal forming conditions - Camberg, Alan Adam; Striewe, Marius; Tröster, Thomas; Bohner, F.; Tölle, J. (5th MATFEM Conference)